1998
DOI: 10.1097/00004032-199812000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Issues in the Reconstruction of Environmental Doses on the Basis of Thermoluminescence Measurements in the Techa Riverside

Abstract: The potential of thermoluminescence measurements of bricks from the contaminated area of the Techa river valley, Southern Urals, Russia, for reconstructing external exposures of affected population groups has been studied. Thermoluminescence dating of background samples was used to evaluate the age of old buildings available on the river banks. The anthropogenic gamma dose accrued in exposed samples is determined by subtracting the natural radiation background dose for the corresponding age from the accumulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 0 publications
2
24
1
Order By: Relevance
“…Initial work by Bougrov et al (1995) had shown that the levels of cumulative dose registered in bricks from the Old Mill, ranged from 1 Gy (walls facing land) to 5 Gy (walls facing the reservoir), and that the cumulative background dose was ∼0.5 Gy arising from the substantial age of the buildings. The latter was checked by dating brick from a heavily shielded location in the mill and the resulting luminescence age of 129 ± 14 years was consistent with available documentary evidence (Bougrov et al, 1998). Although the NNW facing walls of the Old Mill and the Granary are of particular interest because part of the settlement was distributed around the shores of Metlinsky Pond, more recent work has focused on the SW wall of the Old Mill (Fig.…”
Section: Metlinomentioning
confidence: 55%
See 4 more Smart Citations
“…Initial work by Bougrov et al (1995) had shown that the levels of cumulative dose registered in bricks from the Old Mill, ranged from 1 Gy (walls facing land) to 5 Gy (walls facing the reservoir), and that the cumulative background dose was ∼0.5 Gy arising from the substantial age of the buildings. The latter was checked by dating brick from a heavily shielded location in the mill and the resulting luminescence age of 129 ± 14 years was consistent with available documentary evidence (Bougrov et al, 1998). Although the NNW facing walls of the Old Mill and the Granary are of particular interest because part of the settlement was distributed around the shores of Metlinsky Pond, more recent work has focused on the SW wall of the Old Mill (Fig.…”
Section: Metlinomentioning
confidence: 55%
“…When examining the values of DX , Tarenenko et al, 2003and Bougrov et al, 1998 obtained for the SW wall of the Old Mill for the same depth range (10 ± 5 mm) and the same height, an overdispersion (ca 15-20%) was observed, unexpected given the relative proximity (several m) of the sampled locations. Jacob et al (2003) concluded that, although not significantly affecting the median value of DX calculated for each height, some of the overdispersion could be attributed to systematic errors arising from one of the techniques applied.…”
Section: Metlinomentioning
confidence: 90%
See 3 more Smart Citations